98. Quantitative assessment of visual pursuit of salient stimuli in Disorders of Consciousness - Estraneo, A.; Moretta, P.; Trojano, L.; Loreto, V.; Santoro, L. (Clinical neurophysiology, 2013)
A quantitative assessment of visual tracking could help to distinguish Vegetative State (VS) from Minimally Conscious State (MCS) (Trojano, 2011). In the present study we assess whether affective saliency modifies visual tracking in VS and MCS. 13 VS and 13 MCS patients, with traumatic or non-traumatic etiology. Exclusion criteria: lack of visual evoked potentials, premorbid or current ocular pathologies, oculomotor dysfunctions. Eleven age-matched normal subjects were assessed as controls. We recorded visual pursuit by means of a computerized infrared eye-tracker system. Stimuli: a circle, a parrot, and the face of one patient’s relative (5×4cm). All stimuli slowly moved on a pc-monitor (total recording time: 162s). Measures: number of fixations on or off the target. Distribution of on- and off-target fixations differed significantly between MCS and VS. Moreover in MCS the proportion of on- and off-target fixations for relatives’ face was significantly higher than for other stimuli, whereas in VS and controls did not. The proportion of on-target fixations seems able to discriminate MCS and VS. Affective saliency of the stimulus enhances visual tracking in MCS. Although the clinical evaluation represents the gold standard, the present findings can help in differential diagnosis in DoC.